Urological Anomalies in Early Childhood UTI: MCU Detects What Ultrasound Misses - Venugopal, Aishwarya; Soundararajan, Prasanth; Kumar, Nikhil; S.R.Krishnan, Anjana; Bhat Y, Ramesh (Indian Journal of Child Health, 2026)
Background: Urinary tract infection (UTI) is a common serious bacterial infection in young children and may be associated with underlying congenital anomalies of the kidney and urinary tract (CAKUT). Early identification of these anomalies is essential to prevent renal scarring and long-term renal morbidity. However, the optimal imaging strategy following UTI in young children remains debated. This study aimed to determine the prevalence and pattern of urinary tract anomalies in children and to evaluate the diagnostic yield of renal–bladder ultrasonography (RBUS) and micturating cystourethrogram (MCU). Methods: This prospective observational study was conducted in a tertiary care hospital over 1.5 years. Children aged 1 month to 5 years admitted with UTI were included. All participants underwent RBUS and MCU following treatment of the acute infection. Additional imaging was performed when indicated. Vesicoureteral reflux (VUR) was graded according to standard criteria. Results: Ninety-six children were included in the final analysis. RBUS was abnormal in 61.4% of children, most commonly showing hydronephrosis. MCU detected abnormalities in 33.3%, with vesicoureteral reflux identified in 28.1%. High-grade reflux (Grades IV–V) constituted the majority of VUR cases. Notably, 70.3% of children with VUR had a normal RBUS. Renal scarring was detected in a substantial proportion of children with VUR who underwent DMSA scanning. Conclusions: MCU demonstrated a superior diagnostic yield in children with UTI who have underlying urological anomalies compared to ultrasonography, supporting the inclusion of MCU in the initial evaluation of young children with culture-proven UTI, especially in settings with a high burden of congenital uropathies.